PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI UD. BILL NET DI BOTOHILI KECAMATAN LOLOWAU - Restin Angelina Halawa (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
This research aims to determine the influence of service quality on customer satisfaction at UD. Bill Net in Botohili, Lolowau District. The type of research used in this study is quantitative, associative research to examine causal relationships. The population in this study consists of UD. Bill Net customers. The sample in this study is 50 respondents. The data collection technique used in this research is by distributing questionnaires. The research method involves testing instrument validity and reliability, classical assumption tests, tests for data normality and heteroskedasticity, t-test hypothesis testing, coefficient of determination (R2) testing, and data analysis techniques. The results of this study indicate that service quality (X) significantly influences customer satisfaction (Y). The researcher's recommendation is that UD. Bill Net should always prioritize better service quality and customer interests to encourage repeat purchases, always provide friendly service to ensure customer comfort with the service provided, and always respond promptly so that customers feel satisfied with the service they receive.